HOXB 13 Gene Single Nucleotides Polymorphisms as an Early Molecular Marker for Prostate Cancer - Hasanain Ali Shubbar (Journal of Global Pharma Technology, 2018)
New single nucleotide polymorphisms in Hoxb13 gene has a related with prostate cancer and may be considered as early molecular marker and SNPs are located in gene promoters, exons, intronsas well as 5'- and 3'- un translated regions. The study investigation the association between single nucleotide polymorphisms and prostate patients Materials and Methods: 75 prostate cancer patients, 75 prostate benign and 81 healthy were included. A conventional PCR technique was used to defect variable region of HOXB13 gene by using specific primer pairs synthesized targeting certain region of exon one and two in the HOXB13. The DNA sequencing results for 134 samples were analyzed and aligned using NCBI nucleotide alignment tool, BLAST n (Basic Local Alignment Search Tool) in which DNA sequence obtained in this study were compared with human reference HOXB13 gene sequence. Results showed for HOXB13 gene deletion T located in 48728612 region complement (promoter region), substitution C >T Rs 8556 (exon 1 region), deletion A 48727109 region complement (intron region) and substitution G >A region complement.